Persepsi Digitalisasi Keuangan Pedagang Pakaian Di Pasar Tradisional Rengel-Tuban - Masruroh, Dewi; Prabowo, Prayudi Setiawan (Jurnal Ekonomika : INDEPENDEN, 2025)
This study aims to describe the perceptions of clothing traders in Rengel Village Traditional Market regarding financial digitalization. A descriptive qualitative approach was applied using method and source triangulation. Data were collected through structured and semi-structured interviews, direct observations, and photo documentation. The findings reveal that traders’ perceptions vary depending on their understanding, experience, and technology access. Some perceive digital payments such as e-wallets (DANA, OVO), QRIS, and bank transfers as useful (perceived usefulness), but actual use remains limited to bank transfers, often with family assistance. QRIS and e-wallets are still in the introductory stage due to limited technical knowledge. Other obstacles include unstable internet access and limited device ownership.Overall, the acceptance of digital finance among traditional market traders is still at an early stage. Therefore, education, guidance, and infrastructure support are needed to gradually enhance the adoption of financial digitalization in traditional markets.